2013
DOI: 10.1017/s0967199413000361
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gaseous atmosphere and antioxidants on the development and cryotolerance of bovine embryos at different periods ofin vitroculture

Abstract: This study examined the effects of antioxidant supplementation and O2 tension on embryo development, cryotolerance and intracellular reactive oxygen species (ROS) levels. The antioxidant supplementation consisted of 0.6 mM cysteine (CYST); 0.6 mM cysteine + 100 μM cysteamine (C+C); 100 IU catalase (CAT) or 100 μM β-mercaptoethanol (β-ME) for 3 or 7 days of in vitro culture (IVC). Two O2 tensions (20% O2 [5% CO2 in air] or 7% O2, 5% CO2 and 88% N2 [gaseous mixture]) were examined. After 7 days of antioxidant su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 43 publications
(93 reference statements)
1
19
0
2
Order By: Relevance
“…In fact, some studies report different results in which they report that lower O 2 tension yields better developmental rates in bovine embryos (for review see [19]). However, others have reported that higher O 2 tension could be most suitable for IVP in bovine [17], and other studies go further to suggest that low O 2 has negative effects on the rate of embryonic development [60]. As presented here, there are also studies showing that that varying O 2 level does not affect the rate of embryonic development during IVP [61,62].…”
Section: Discussionsupporting
confidence: 58%
“…In fact, some studies report different results in which they report that lower O 2 tension yields better developmental rates in bovine embryos (for review see [19]). However, others have reported that higher O 2 tension could be most suitable for IVP in bovine [17], and other studies go further to suggest that low O 2 has negative effects on the rate of embryonic development [60]. As presented here, there are also studies showing that that varying O 2 level does not affect the rate of embryonic development during IVP [61,62].…”
Section: Discussionsupporting
confidence: 58%
“…These studies used group culture dynamics and had differences in the media used, which may explain our differing results. Moreover, many studies have seen no or detrimental effects when comparing the culture of presumptive bovine embryos in 5% O 2 as opposed to in air (Mingoti, Castro, Mao, Sa Barretto, & Garcia, ; Rocha‐Frigoni, LeãoLeao, Nogueira, Accorsi, & Mingoti, ; Somfai et al, ). It has been suggested that when presumptive zygotes are cultured in the presence of cumulus cells they show improved blastocyst rates at higher O 2 levels than in the hypoxic 5% O 2 conditions (Corrêa, Rumpf, Mundim, Franco, & Dode, ).…”
Section: Discussionmentioning
confidence: 99%
“…This stress results from an imbalance between ROS and antioxidant substances, with a predominance of the former (ROCHA-FRIGONI et al, 2015). ROS are represented by a variety of molecules and free radicals produced from oxygen metabolism in biological systems.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…From this radical, other biochemical reactions can lead to the formation of hydrogen peroxide (H 2 O 2 ) and the hydroxyl radical (•OH) (TAKAHASHI, 2012). All these oxygen-derived metabolites exhibit high instability and reactivity due to at least one unpaired electron in their outer orbit (ROCHA-FRIGONI et al, 2015).…”
Section: Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation